PERANAN MAYOR ABDULLAH DALAM MEMPERTAHANKAN KEMERDEKAAN REPUBLIK INDONESIA PADA TAHUN 1945-1949 DI PEKANBARU - Nopriadi Siswanto; Tugiman Tugiman; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Major Abdullah is one of the military figures of the Indonesian National Police who maintained independence from the Republic of Indonesia in Pekanbaru in 1945-1949. Major Abdullah was born on February 3, 1932 in Pekanabaru by parents named Ibrahim and Aisha. Major Abdullah was the second of four children who defended the independence of the Republic of Indonesia in Pekanbaru in 1945-1949. The purpose of this study was to determine the background of Major Abdullah's life, to determine Major Abdullah's role in maintaining the independence of the Republic of Indonesia in Pekanbaru in 1945-1949, to end Major's struggle To find out Abdullah in maintaining the independence of the Republic of Indonesia in Pekanbaru in 1945-1949 and to learn the prize Major Abdullah received from the government. Data analysis uses a historical writing method that consists of several stages, namely heuristics, verification, interpretation and historiography. The results of this study are the role of Major Abdullah as the right-hand man of Lt. Col. Hasan Basri, then became the president of the student army platoon flying the red and white flags in Pekanbaru and became an information courier in the Moutbatten Hotel attack. in Pekanbaru for Lieutenant Colonel Hasan Basri. After the end of the battle in 1945-1949, Major Abdullah returned to the National Police Force until 1986. When he retired, Major Abdullah joined the Indonesian Veterans Legion Organization.Key Words: Major Abdullah, Role, Defend Independence